Monocyte human leukocyte antigen-DR-mediated diabetic nephropathy progression is a promising therapeutic target - Wang, Yue; Fu, Shaojie; Su, Sensen; Xu, Zhonggao (Frontiers in Endocrinology, 2025)
ObjectiveIncreasing evidence has suggested that immune cells are known to play a pivotal role in the progression of diabetic nephropathy (DN). However, the specific causal role of monocyte surface markers, particularly human leukocyte antigen-DR (HLA-DR), remains unclear. This study aims to investigate the causal relationship between monocyte HLA-DR expression and DN risk and to validate its clinical relevance.MethodsWe first employed a detailed two-sample Mendelian randomization (MR) analysis to investigate the potential causal relationships involving immune cell signatures particularly monocytes and DN risk. Then, to clinically validate these findings, we used flow cytometry to detect the median fluorescence intensity (MFI) of HLA-DR on monocyte in peripheral blood from DN patients and normal controls and analyzed its correlation with key renal function indicators of DN patients.ResultsTwo monocyte-related immune cell signatures were identified significantly associated with DN risk via MR analyses after false discovery rate (FDR) correction: HLA-DR on CD14+ CD16− monocyte (OR = 1.189, 95% CI: 1.113–1.270, PFDR = 1.83 × 10−4) and HLA-DR on CD14+ monocyte (OR = 1.188, 95% CI: 1.107–1.276, PFDR = 6.69 × 10−4), as determined by the inverse variance weighting method. The MFI of HLA-DR on CD14+ CD16− (p <0.001) and CD14+ monocyte (p <0.05) was higher in DN patients compared with normal controls, respectively. Clinical validation confirmed that the elevated HLA-DR MFI on these monocyte subsets was significantly correlated with worsening renal function, showing positive correlations with serum creatinine levels and negative correlations with estimated glomerular filtration rate.ConclusionsOur findings demonstrate that the elevated MFI of HLA-DR on CD14+ and CD14+ CD16− monocyte is associated with DN and is significantly associated with worsened renal function, highlighting monocyte HLA-DR as a key immune mediator in DN progression and a promising therapeutic target for intervention.